Victimization and Mobility Intentions: Accounting for Neighborhood Perceptions in Central American Contexts - Iesue, Laura (Victims & offenders, 2025)
Although the topics of victimization, neighborhood perceptions and mobility intentions are researched in Western contexts, the extant work linking these topics is noticeably absent in the Central American contexts of Guatemala, El Salvador, and Honduras even though past victimization has been found to be a salient predictor of migration to the United States from these countries. This study uses United States Agency for International Development (USAID) and Vanderbilt University’s data from an impact evaluation of USAID’s Community-Based Crime and Violence Prevention Approach in Central America and mixed effect multi-level logistic regression models to examine whether perceptions of neighborhoods are associated with a greater mobility risk, and whether this is also heightened among individuals who had previously been a victim. Results show that victimization predicts mobility intentions, followed by the traditional “push factors” of migration more than neighborhood perceptions in all three country contexts. However, social cohesion seems to be the most relevant predictor of mobility compared to other neighborhood factors. More research should focus on the indirect effects of neighborhood perceptions, victimization, and demographic characteristics on mobility and consider how perceptions are impacted by cultural differences across country contexts.